2017
DOI: 10.1002/cvj.12057
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ethical Information Resources on Independently Licensed Counselors

Abstract: A random sample of 430 independently licensed counselors evaluated 4 ethical information interventions in the context of 16 boundary‐crossing scenarios. Results indicated that counselors have serious reservations about any form of boundary crossing. They reported mostly reviewing various codes of ethics, reviewing state laws and rules, consulting with others, working from gut instincts, and reflecting on personal experience when confronted with boundary‐crossing issues. Participants clearly preferred streamlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The associated hypothesis was that students' ethical decision-making strategies would rely more heavily on the Code of Ethics and ethical decision-making models as compared to independently licensed counselors because students are in a training program. Burns and Cruikshanks (2017b) found that independently licensed counselors dropped out of the Gottlieb group significantly more than the other three groups. Lastly, the researcher examined if participant drop-out rates would be equal among the four ethical information resources.…”
Section: Purposementioning
confidence: 91%
See 2 more Smart Citations
“…The associated hypothesis was that students' ethical decision-making strategies would rely more heavily on the Code of Ethics and ethical decision-making models as compared to independently licensed counselors because students are in a training program. Burns and Cruikshanks (2017b) found that independently licensed counselors dropped out of the Gottlieb group significantly more than the other three groups. Lastly, the researcher examined if participant drop-out rates would be equal among the four ethical information resources.…”
Section: Purposementioning
confidence: 91%
“…However, the effectiveness of these ethical information resources in assisting counselors to make better boundary crossing decisions with clients has not been proven. Researchers report one instance where an ethical information resource appeared more effective than another in studies with independently licensed counselors, counselor educators, and counselor education students (Burns, 2019;Burns & Cruikshanks, 2017b, 2019. Burns (2019) and Burns and Cruikshanks (2019) researched the use of three ethical information resources and a placebo with counselor educators and counselor education students by having each group separately rate 16 boundary crossings that could occur between the two groups.…”
Section: Impact Of Ethical Information Resources On Counselors Negotiating Boundary Crossingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two hundred twenty‐four participants completed the study, which resulted in a 17% response rate. For comparison, four different studies that included independently licensed counselors, counselor educators, or counselor education students achieved response rates between 12% and 24% (Burns & Cruikshanks, , , , in press). According to Erford (), “usually, response rates for mailed or electronic surveys are less than 20 percent” (p. 192).…”
Section: Methodsmentioning
confidence: 99%
“…Although ethical decision‐making models are intended to offer better guidance than only reviewing ethics codes (Barnett et al, ; Kitchener, ), researchers have not demonstrated that the use of ethical decision‐making models ultimately results in “better” decision‐making (Barnett et al, ; Burns & Cruikshanks, ). Future researchers could help counselor educators, professional counseling organizations, and state counseling licensure boards better understand the impact of ethical informational resources on counselor education students when they are faced with boundary crossings during training.…”
Section: Ethical Decision‐making In Counselor Education Training Progmentioning
confidence: 99%